TOWARD A PUTATIVE PARADIGM SHIFT IN DIRECT PULP CAPPING - Alexandru-Andrei Iliescu; Kamel Earar; Gabi Topor; Andrei Iliescu (Romanian Society of Oral Rehabilitation, 2019)
Conventionally the cases accepted for direct pulp capping are the inadvertently exposed normal pulps and carious exposures in teeth without apical radiolucency. The recent advances in dental materials, namely the bioceramics, allowed successful vital therapy by direct pulp capping even in young permanent teeth with irreversible pulpitis. The choice of pulp capping material is pivotal in pulp vital therapy of carious exposures as tricalcium silicates shift the balance inflammation-healing toward the regeneration of damaged dentin-pulp complex. Anticipating a reliable outcome, the high anti-inflammatory potential and modulating capacity of cytokines and growth factors proved by bioactive endodontic cements in direct pulp capping should be associated with new molecular diagnostic tests and cautious clinical evaluation. However, it seems that a paradigm shift is expected in the decision of direct pulp capping.